The atomic bazaar : the rise of the nuclear poor - Langewiesche, William (New York : Farrar, Straus and Giroux, 2007)
Journalist Langewiesche investigates the burgeoning global threat of nuclear weapons production. This is the story of the inexorable drift of nuclear weapons technology from the hands of the rich into the hands of the poor. As more unstable and undeveloped nations find ways of acquiring the ultimate arms, the stakes of state-sponsored nuclear activity have soared to frightening heights. Even more disturbing is the likelihood of such weapons being manufactured and deployed by guerrilla non-state terrorists. Langewiesche also recounts the recent history of Abdul Qadeer Khan, the scientist at the forefront of nuclear development and trade in the Middle East who masterminded the theft and sale of centrifuge designs that helped to build Pakistan's nuclear arsenal, and who single-handedly peddled nuclear plans to North Korea, Iran, and other potentially hostile countries. He then examines in dramatic and tangible detail the chances for nuclear terrorism.--From publisher description.
The vanguard of the poor -- Nukes without nations -- The wrath of Khan -- The point of no return.
Keywords: Nuclear weapons; Nuclear weapons -- Pakistan; Nuclear nonproliferation; World politics -- 21st century